Determinan yang Berhubungan dengan Upaya Pencegahan Infeksi Menular Seksual pada Wanita Pekerja Seks di Jakarta Timur: Determinants Related to Efforts for Prevent Sexually Transmitted Infections among Female Sex Workers in East Jakarta - Niken Purbowati; Elly Dwi Wahyuni; Aticeh Aticeh (Jurnal Bidan Cerdas, 2022)
Introduction: Female sex workers (FSWs) are high-risk group for exposure to STIs and HIV. FSWs are particularly vulnerable to STIs, HIV. Only about one in three FSWs receive adequate STIs, HIV prevention services and medical care. Objective: to analyze the relationship between knowledge, perceptions and support of community counselors on STIs prevention in FSWs. Method: Quantitative research with  analytic cross-sectional design. The population of this study is female sex workers in the Jingga Cipinang Community, East Jakarta. The sampling technique used was snowball sampling. Data were analyzed by chi square test and logistic regression risk model. Results: Perception variables, support from community counselors and support from health workers are associated with STIs prevention in FSWs. The results of the analysis showed that the most dominant variable was knowledge (p=0,0001) after being controlled by the information source variable, with the OR value of the knowledge variable 56.2. The multivariate model can explain that FSWs who have good knowledge will do 56 times better to prevent STIs than those whose knowledge is less after being controlled by the variable information sources. Conclusions: Knowledge of sexual and reproductive health (SRH) should reflect two main topics, namely how to promote efforts to prevent and protect women from STIs.   ABSTRAK Pendahuluan: Wanita pekerja seks (WPS) merupakan salah satu kelompok risiko tinggi terpapar IMS dan HIV. WPS sangat rentan terhadap HIV, hanya sekitar satu dari tiga WPS menerima layanan pencegahan HIV yang memadai dan perawatan medis. Tujuan: untuk menganalisis hubungan pengetahuan, persepsi dan dukungan pembimbing komunitas terhadap pencegahan IMS padaWPS. Metode: Penelitian kuantitatif dengan desain cross-sectional yang bersifat analitik. Populasi penelitian ini adalah Wanita pekerja seks di Komunitas Jingga Cipinang Jakarta Timur. Teknik pengambilan sampling menggunakan snowball sampling. Data dianalisis dengan uji chi square dan regresi logistic model risiko. Hasil: Variabel persepsi, dukungan pembimbing komunitas dan dukungan tenaga kesehatan berhubungan dengan pencegahan IMS pada wanita pekerja seks (WPS). Hasil analisis didapatkan variabel yang paling dominan adalah pengetahuan (p=0,0001) setelah dikontrol variabel sumber informasi, dengan nilai  OR dari variabel pengetahuan 56,2. Model multivariate tersebut dapat dijelaskan bahwa WPS yang mempunyai pengetahuan baik akan melakukan pencegahan infeksi menular seksual 56 kali lebih baik dibandingkan yang pengetahuannya kurang setelah dikontrol oleh variabel sumber informasi. Kesimpulan: Pengetahuan kesehatan reproduksi dan seksual sebaiknya mencerminkan dua topik utama, yaitu bagaimana caranya mempromosikan upaya pencegahan dan melindungi wanita dari IMS.